2019
DOI: 10.1177/1120700019873886
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-assisted technique in total hip arthroplasty can improve the precision of acetabular cup placement: a randomised controlled trial

Abstract: Background: Malposition of the acetabular component mainly results from intraoperative pelvic motion and manual errors during cup placement. We investigated the outcomes of a device that uses a level indicator application of a smartphone to function as a pelvic tilt goniometer to assess intraoperative motion. The cup positions outside Lewinnek’s safe zone were compared between the smartphone-assisted technique and the conventional method that uses a mechanical alignment guide. Methods: A randomised controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Dynamic planning has to be accurately reproduced in the operating room to finalize the functional advantages. The malposition of components mainly results from the errors in patient positioning, intraoperative pelvic motion and manual errors during the surgery [ 43 ]. Traditional free hand techniques successfully achieve target ranges for both inclination and anteversion in only 47% of cases with other studies reporting even lower rates [ 20 , 21 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dynamic planning has to be accurately reproduced in the operating room to finalize the functional advantages. The malposition of components mainly results from the errors in patient positioning, intraoperative pelvic motion and manual errors during the surgery [ 43 ]. Traditional free hand techniques successfully achieve target ranges for both inclination and anteversion in only 47% of cases with other studies reporting even lower rates [ 20 , 21 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 80% to 96% of components were placed in the safe zone using computer navigation while 100% were placed using robotics. In our series, all of the postoperative acetabular components were within Lewinnek’s safe zone [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature regarding acetabular cup placement is quite extensive, while there are limited data on the femoral stem position [15,19,22]. The recent literature agrees regarding the relevance of femoral osteotomy planning for a successful THA; the femoral cut mainly affects the leg length, the hip offset, and the tracking of the implant [21,36].…”
Section: Discussionmentioning
confidence: 99%